1991
DOI: 10.1038/bjc.1991.118
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intra-arterial vasoconstrictors on the distribution of a radiolabelled low molecular weight marker in an experimental model of liver tumour

Abstract: Regional delivery of angiotensin II and phenylephrine caused significantly greater retention of marker in tumour than liver with an overall 4-fold increased retention of marker one minute after its injection. Ninety minutes after injection there was still significant retention of marker compared to control animals. Regional delivery of hepatic artery vasoconstrictors increase delivery of marker and may increase delivery of chemotherapeutic drug to liver tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Neben der Gabe von abbaubaren Stärkepartikeln sowie Noradrenalin und Angiotensin II, welche vor allem die Perfusion der nicht tumorbefallenen Restleber einschränken [12,32], kann dies auch [24]. Neben der Gabe von abbaubaren Stärkepartikeln sowie Noradrenalin und Angiotensin II, welche vor allem die Perfusion der nicht tumorbefallenen Restleber einschränken [12,32], kann dies auch [24].…”
Section: Pharmakologische Grundlagenunclassified
“…Neben der Gabe von abbaubaren Stärkepartikeln sowie Noradrenalin und Angiotensin II, welche vor allem die Perfusion der nicht tumorbefallenen Restleber einschränken [12,32], kann dies auch [24]. Neben der Gabe von abbaubaren Stärkepartikeln sowie Noradrenalin und Angiotensin II, welche vor allem die Perfusion der nicht tumorbefallenen Restleber einschränken [12,32], kann dies auch [24].…”
Section: Pharmakologische Grundlagenunclassified
“…A randomised trial has suggested that HAI chemotherapy improves the survival rate compared with untreated controls (Hunt et al, 1990). There is some evidence that co-administration of vasoactive agents such as angiotensin II (AT II) can improve the efficacy of HAI chemotherapy (Goldberg et al, 1991;Hemingway et al, 1991a). However, Sasaki et al (1985) have shown that AT II reaches the peak of its action at about 100 s from the start of the infusion.…”
mentioning
confidence: 99%
“…Local intra-arterial administration of angiotensin II to hepatic tumours and liver metastases also has potential for improving regional chemotherapy of these tumours (Sasaki et al, 1985;Hemingway et al, 1991 andGoldberg et al, 1991 (Hori et al, 1985;Burton et al, 1985). Trotter et al (1991) One of the tail vein catheters was fitted with a T-piece connector allowing two syringes to be connected to it.…”
mentioning
confidence: 99%